2000
DOI: 10.1016/s0092-8674(00)80871-5
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of T7 Gene 4 Ring Helicase Indicates a Mechanism for Sequential Hydrolysis of Nucleotides

Abstract: We have determined the crystal structure of an active, hexameric fragment of the gene 4 helicase from bacteriophage T7. The structure reveals how subunit contacts stabilize the hexamer. Deviation from expected six-fold symmetry of the hexamer indicates that the structure is of an intermediate on the catalytic pathway. The structural consequences of the asymmetry suggest a "binding change" mechanism to explain how cooperative binding and hydrolysis of nucleotides are coupled to conformational changes in the rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
539
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(565 citation statements)
references
References 49 publications
(1 reference statement)
26
539
0
Order By: Relevance
“…We propose that the side chain of Asn 149 contributes to the catalytic site geometry that allows for the high turnover rates of PspF. Our functional assignment is in agreement with the previously suggested roles of the second sensor I residue in other AAAϩ proteins (37,38).…”
Section: The Asparagine Of the Pspf Sensor I Is Involved In Atp Hydrosupporting
confidence: 90%
“…We propose that the side chain of Asn 149 contributes to the catalytic site geometry that allows for the high turnover rates of PspF. Our functional assignment is in agreement with the previously suggested roles of the second sensor I residue in other AAAϩ proteins (37,38).…”
Section: The Asparagine Of the Pspf Sensor I Is Involved In Atp Hydrosupporting
confidence: 90%
“…Therefore, we propose a model in which TrwB operates as a molecular motor, translocating DNA by a mechanism similar to that used by F 1 -ATPase. A somehow similar mechanism has been proposed for DNA movement across T7 gene4 hexameric helicase (10,27).…”
Section: Discussionmentioning
confidence: 55%
“…This result suggests that hetero-oligomers are formed and that the presence of a wild-type linker region can dissipate the extensive oligomerization. These results are interesting in view of the earlier finding that a T7 gene 4 helicase domain having a deletion in this portion of the linker region formed extended oligomers in the crystal structure rather than hexamers (9) whereas the helicase domains containing this portion of the linker region crystallized as hexamers (10).…”
Section: T7 Helicase-primase Linker Regionmentioning
confidence: 68%
“…Biochemical data suggested that this linker region is critical for the functioning of the gene 4 protein (8). As anticipated from the biochemical data, crystal structures of the helicase domains revealed residues in the linker of one subunit of the hexamer contacting residues in the adjacent subunit, thus contributing to the stability of the hexamer (9,10). Although the structure showed clearly the participation of the linker in subunit interaction, 9 of 26 residues were disordered in the structure.…”
Section: Screening Of Permutable Amino Acid Changes At Specific Positmentioning
confidence: 71%
See 1 more Smart Citation